Dependence of riparian communities on ecosystem services in northern Ghana - Mul, Marloes L.; Pettinotti, L.; Amonoo, Naana Adwoa; Bekoe-Obeng, E.; Obuobie, Emmanuel (International Water Management Institute, 2017)
This study investigated the dependence of three riparian communities on ecosystem services in northern Ghana. Participatory mapping and ranking exercises in gender-segregated groups were used to elicit information on the communities’ livelihoods. The most important ecosystem-based activities (EBA) are farming, fishing, livestock watering and grazing, collection of wild fruits and vegetables, and provision of water for domestic use. The major EBA are dependent on the seasonal flows of the White Volta River, which are under pressure due to climatic and other anthropogenic changes. For example, observed delays in the start of the rainy season are affecting rainfed agricultural activities on the floodplains. Delayed planting on the floodplains results in damage to, or loss of, crops as floods arrive before the harvest. Moreover, the Bagré Dam in Burkina Faso, built upstream of the communities, has impacted the natural river flow. The planned Pwalugu Dam may, depending on the final operations, support or affect EBA. We, therefore, recommend that operations of the Pwalugu Dam should take into consideration the flow requirements of EBA downstream of the dam.